ANALISIS PERBANDINGAN VOLUME PERDAGANGAN SAHAM SEBELUM DAN SESUDAH STOCK SPLIT PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Jumady, Edy; Halim, Ardiansyah (Jurnal Ecoment Global, 2020)
This study aims to examine and analyze differences in stock trading volumes before and after stock splits in manufacturing companies on the IDX. The design of this study uses a quantitative descriptive approach with a sample of 3 companies and an observation period of 10 days before and 10 days after a stock split so that the observation sample is 60 observation periods. Data analysis method used in hypothesis testing is t-test regression.The results of the study provide evidence that the average trading volume there is a significant difference before and after the stock split in manufacturing companies listed on the Indonesia Stock Exchange in 2016. These results support the hypothesis, so the hypothesis is accepted.Keywords: Stock Trading Volume, Stock Split, t-tes regresion